Polyphyllin VII ameliorates neuroinflammation and brain injury via modulating Treg/Th17 balance in a mouse model of cerebral ischemia-reperfusion injury - Sang, Qiuling; Kang, Chunyang; Liu, Dingxi; Wang, Libo; Liu, Xiaoyang; Li, Jia (International immunopharmacology, 2024)
•Polyphyllin VII reduced infarct volume, ameliorated brain injury and neuroinflammation, and improved long-term functional recovery of MCAO mice.•Polyphyllin VII increased infiltration of Treg cells and suppressed infiltration of Th1/Th17 cells in ischemic brain.•Polyphyllin VII suppressed mTORC1 activation to influence glycolytic metabolism and ROS generation of T cells. Dysregulation of Th17 and Treg cells contributes to the pathophysiology of cerebral ischemia. Metabolic changes of peripheral CD4+ T cells lead to the imbalance of Treg/Th17 polarization, which represents a promising strategy for post-stroke therapy. Polyphyllin VII (PVII), a steroidal saponin extracted from traditional Chinese herb Rhizoma Paridis, has multiple bioactivities, but the potential function of PVII in cerebral ischemia–reperfusion injury is not elucidated yet. In our study, a mouse transient middle cerebral artery occlusion (MCAO) model was constructed. TTC staining, H&E staining, TUNEL staining, ELISA assay, flow cytometry, western blot, RT-qPCR, Open-field test, Morris water maze test, hanging wire test, rotarod test and foot-fault test were performed to evaluate the potential function of PVII in MCAO mice. We found that PVII showed protective effects on cerebral ischemia–reperfusion injury by reducing infarct volume, ameliorating brain injury and neuroinflammation, and improving long-term functional recovery of MCAO mice. PVII promoted Treg infiltration and suppressed infiltration of Th1/Th17 cells in ischemic brain in vivo. Moreover, PVII impaired peripheral CD4+ T cell activation and modulated Treg/Th17 differentiation in vitro. Mechanistically, PVII suppressed mTORC1 activation to influence glycolytic metabolism and ROS generation of T cells, thus leads to the imbalance of Treg/Th17 polarization towards Treg skewed. Furthermore, reactivation of mTORC1 by MHY1485 abolished the influence of PVII on brain injury and neuroinflammation in MCAO mice. Our data provided a novel role of PVII in cerebral ischemia–reperfusion injury via manipulating Treg/Th17 imbalance.